Kingdom of Lesotho Local Governance, Decentralization, and Demand-Driven Service Delivery, Volume 1. Main Report - World Bank (Washington, DC, 2014)
After more than 35 years, the elected local government system in Lesotho was reestablished in 2005 through the election of the Local Authorities, i.e. the Community and District Councils (CCs and DCs). Across the political spectrum, the political will to move forward was at its peak. An exemplary campaign to educate the entire population as to the purposes and functioning of the new Local Authorities, and the electoral process preceded the election. The purposes of the new system are the improvement in services and access to government, broad participation of the local population in their own development combined with enhanced accountability to them, and promotion of equitable development in all parts of the country. The establishment of the Local Authorities and their election was received by even the remotest populations with great enthusiasm, and the elected Councilors have taken up their job with energy and commitment. The objectives of this report derive from the general priorities of the Poverty Reduction Strategy (PRS) of Lesotho which emphasizes pro-poor growth, community empowerment, improved governance and public sector performance. The specific priorities of the PRS have been set as employment creation, food security, and infrastructure development, deepening of democracy, governance, safety and security, access to health services, increasing human resource capacity, managing and conserving the environment, and improving public service delivery. Cross cutting priorities include combating HIV and AIDS, and addressing gender inequalities as well as issues related to children and youth. From among all the possible sectors, agriculture and natural resources were selected because: (i) the local authorities have a mandate for the promotion of economic development and the management of natural resources; (ii) improvements in these areas are necessary for economic development, poverty reduction, and for improving the tax base and revenue generation capacity; and (iii) improvements require collaboration between local authorities, communities, sector institutions, and the private sector, a collaboration in which the Local Authorities sit at the center of the network of co-producers.